2017
DOI: 10.1123/ijspp.2015-0738
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Sets: Permitting Greater Mechanical Stress Without Decreasing Relative Velocity

Abstract: These data show that the intraset rest provided in CS4 and CS2 allowed for greater external loads than with TS, increasing TW and TUT while resulting in similar PP and %VL. Therefore, cluster-set structures may function as an alternative method to traditional strength- or hypertrophy-oriented training by increasing training load without increasing %VL or decreasing PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 18 publications
1
56
1
Order By: Relevance
“…Nevertheless, implementation of inter-set rest intervals allows for a greater RT volume to be achieved for a particular external load when compared with a traditional scheme of sets [44,45] in trained and untrained men, possibly providing an additional stimulus for muscle hypertrophy. However, it should be noted that cluster sets induce less metabolic stress, but greater emphasis is placed on mechanical stress due to the use of higher training intensities of effort in comparison with traditional sets [44][45][46]71]. Thus, the implementation of cluster sets with short inter-set rest intervals could be a useful strategy to carry out high-volume sessions of high-loads, while keeping a high time-efficiency of training (training volume/time).…”
Section: Cluster Sets Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, implementation of inter-set rest intervals allows for a greater RT volume to be achieved for a particular external load when compared with a traditional scheme of sets [44,45] in trained and untrained men, possibly providing an additional stimulus for muscle hypertrophy. However, it should be noted that cluster sets induce less metabolic stress, but greater emphasis is placed on mechanical stress due to the use of higher training intensities of effort in comparison with traditional sets [44][45][46]71]. Thus, the implementation of cluster sets with short inter-set rest intervals could be a useful strategy to carry out high-volume sessions of high-loads, while keeping a high time-efficiency of training (training volume/time).…”
Section: Cluster Sets Techniquementioning
confidence: 99%
“…Thus, the implementation of cluster sets with short inter-set rest intervals could be a useful strategy to carry out high-volume sessions of high-loads, while keeping a high time-efficiency of training (training volume/time). Furthermore, cluster sets may serve as an alternative to traditional sets for promoting muscle hypertrophy over time during parallel periodization models [46], and prevent monotony in training. Moreover, future studies should investigate the direct effects of cluster sets on exercise-induced muscle growth.…”
Section: Cluster Sets Techniquementioning
confidence: 99%
“…The main findings of this study showed that performing either traditional or cluster set configuration did not affect the main parameters of the countermovement jump. Many research studies been conducted the effect of cluster set during resistance training or plyometric training on athlete performance [14,20,24,25,26,27]. However, the literature on the effect of cluster set on the complex training is scant and does not provide clear conclusion in regards to the acute effect of cluster set on power performance [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, balance between PAP and fatigue during complex training is very crucial to ensure the attainment of optimal explosive power performance. Therefore, the insertion of short inter-repetition rest periods of between 15-45 s [14] during exercise may be one of the best strategies to maintain or enhance power in complex training [15].…”
Section: Introductionmentioning
confidence: 99%
“…All kinetic and kinematic data were collected during the concentric phase of the squat unless noted otherwise using similar methodology to previous research. [18][19][20]…”
Section: Data Acquisitionmentioning
confidence: 99%